Emerging Roles of Mast Cells in the Regulation of Lymphatic Immuno-Physiology - Pal, Sarit; Nath, Shubhankar; Meininger, Cynthia J.; Gashev, Anatoliy A. (Frontiers in Immunology, 2020)
Mast cells (MCs) are abundant in almost all vascularized tissues. Furthermore, their anatomical proximity to lymphatic vessels and their ability to synthesize, store and release a large array of inflammatory and vasoactive mediators emphasize their significance in the regulation of the lymphatic vascular functions. As a major secretory cell of the innate immune system, MCs maintain their steady-state granule release under normal physiological conditions; however, the inflammatory response potentiates their ability to synthesize and secrete these mediators. Activation of MCs in response to inflammatory signals can trigger adaptive immune responses by dendritic cell-directed T cell activation. In addition, through the secretion of various mediators, cytokines and growth factors, MCs not only facilitate interaction and migration of immune cells, but also influence lymphatic permeability, contractility, and vascular remodeling as well as immune cell trafficking through the lymphatic vessels. In summary, the consequences of these events directly affect the lymphatic niche, influencing inflammation at multiple levels. In this review, we have summarized the recent advancements in our understanding of the MC biology in the context of the lymphatic vascular system. We have further highlighted the MC-lymphatic interaction axis from the standpoint of the tumor microenvironment.